EMPOWERING STARTUP COMPANIES WITH ARTIFICIAL INTELLIGENCE TECHNOLOGY - Akbar Firdaus; Winasis, Shinta (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Startup companies have emerged as a crucial pillar of Indonesia's economy, owing to their ability to rapidly adapt to various situations and their role in attracting foreign investment. Currently, the number of startups in Indonesia ranks among the top six globally and contributes approximately 10% to the country's Gross Domestic Product (GDP). Nevertheless, the number of companies that have achieved unicorn and decacorn status still lags significantly behind neighboring countries such as Singapore and India. To enhance investor interest in startups, it is essential to highlight various aspects that startups offer in comparison to competitors, including products or services, market opportunities, growth potential, business models, and innovations. In this context, many startups are leveraging Artificial Intelligence (AI) technology to improve their business performance. This research aims to analyze the functions and advantages of utilizing AI within the startup ecosystem, as well as its impact on enhancing attractiveness and business performance, thereby drawing greater attention from investors. This study employs a literature review method, with the expectation that the findings will provide insights into the use of AI for empowering startups in enhancing their business performance. Keywords : Startup, Artificial Intelligence, Business Performance